73 INHIBITION OF HEME OXYGENASE ACTIVITY FOLLOWING REPEATED HEME LOADS BY TIN MESOPORPHYRIN IN NEWBORN MICE. Issue 1 (1st January 2007) - Wong, R. J.; Morioka, I.; Muchova, L.; Vreman, H. J.; Stevenson, D. K.
Abstract : Heme oxygenase (HO) is the rate-limiting enzyme in the degradation of heme and produces equimolar amounts of carbon monoxide (CO), iron, and bilirubin. Because excess bilirubin production due to increased heme loads (ie, hemolysis) can lead to the development of jaundice, the use of competitive HO inhibitors, such as tin mesoporphyrin (SnMP), may be an ideal treatment strategy for the prevention of pathologic neonatal jaundice (or hyperbilirubinemia). Our objective was to determine the effect of SnMP on HO activity following heme loading in newborn mice. Seven-day-old mice were administered 30 μM hemin (H) by subcutaneous (SQ) injection on day 1. On the second day, mice were administered with 30 or 3.75 μM SnMP (SnMP30 or SnMP3.75, respectively) or vehicle (V) by direct intragastric injections. On day 3, V or a second H load was injected SQ again. On the fourth day, mice were sacrificed and liver, spleen, and brain harvested for quantitation of HO activity using gas chromatography. %HO activity compared to the H-V-V Group (mean ± SD) for each group ( n = 4-6 per group) is shown in the table below: In the H-SnMP30 -V group, HO activity was significantly inhibited in all tissues. In the H-SnMP3.75 -V group, liver and spleen were inhibited at the same level as that of the H-SnMP30 -V group, but without inhibition of brain HO activity. Following a second heme load (H-V-H group), HO activity increased 36%, 27%, and 15% in liver, spleen, and brain, respectively. In the H-SnMP30 -H group, HO activity was still significantly inhibited in all tissues. In contrast, for the H-SnMP3.75 -H group, HO activity was no longer inhibited. We conclude the administration of 30 and 3.75 μM SnMP was similarly potent after a single heme load. However, after a second heme load, only SnMP at a dose of 30 μM was effective in inhibiting not only liver HO activity but also that of the brain. These findings show that low doses of SnMP do not exert long-term inhibition of HO activity in the context of repeated heme loads. This work was supported by National Institutes of Health grants #HL68703 and HD58013.